2011
DOI: 10.1007/s11255-011-9903-3
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of end-stage renal disease in Nigeria: the way forward

Abstract: The incidence of CKD (Chronic kidney disease) in Nigeria has been shown by various studies to range between 1.6 and 12.4%. We have shown that the burden of renal disease in Nigeria is probably significantly higher than any previous study on end-stage renal disease (ESRD) has documented, as most studies are hospital-based and fail to include the many patients who do not have access to hospital care. The increased prevalence of ESRD among blacks in the United States and South Africa compared with other races als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 30 publications
2
33
2
Order By: Relevance
“…The commonest causes of ESRD among our patient population were hypertension and glomerulonephritis; together accounting for about 60% of cases. This finding is similar to that reported from other parts of Nigeria, and sub‐Saharan Africa . However, diabetes was responsible for a significant proportion of cases of ESRD in this study being the third commonest cause of ESRD; a finding similar to that reported by Egha et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The commonest causes of ESRD among our patient population were hypertension and glomerulonephritis; together accounting for about 60% of cases. This finding is similar to that reported from other parts of Nigeria, and sub‐Saharan Africa . However, diabetes was responsible for a significant proportion of cases of ESRD in this study being the third commonest cause of ESRD; a finding similar to that reported by Egha et al .…”
Section: Discussionsupporting
confidence: 92%
“…and Ojogwu et al. in two separate studies None of the ESRD patients had an arteriovenous fistula created prior to commencement of hemodialysis as recommended by the Kidney Disease Quality Outcomes Initiative and Fistula First Initiative guidelines . In fact, repeated cannulation of the femoral vein was the initial vascular access for dialysis in all the patients with only a small proportion migrating to a nontunneled internal jugular catheter after it became technically difficult to access the circulation via cannulation of the femoral vein.…”
Section: Discussionmentioning
confidence: 97%
“…In Nigeria, it ranked with chronic glomerulonephritis as the most commonly implicated among the causes of CKD. [14] About 40% of the subjects in this study had elevated BP, this was high when compared with reports of various studies in other Niger Delta communities in the country. [15][16][17] However, Akpa et al [18] reported a similar prevalence rate (40.8%) in a survey of a Niger Delta community in Rivers state.…”
Section: Sociodemographicmentioning
confidence: 43%
“…This is consistent with other study on hypertension and other noncommunicable diseases. [9][10][11][12][13][14][15][16][17][18] …”
Section: Sociodemographicmentioning
confidence: 99%
See 1 more Smart Citation